Evaluating the reactivity of pyrite on Mars under current and ancient geochemical environments - Gil-Lozano, C.; Mateo-Martí, E.; Gago-Duport, L.; Losa-Adams, E.; Sampedro, M. Fernández; Bishop, J. L.; Chevrier, V.; Fairén, A. G. (Frontiers in Astronomy and Space Sciences, 2025)
Alteration of pyrite-bearing basalt on Mars could provide an important source of sulfates, iron oxides/hydroxides and amorphous silica. Natural semiconducting minerals can undergo photooxidation reactions under UV irradiation due to the generation of electron holes. In this work, we experimentally investigate the photocatalysis of pyrite (FeS2)-olivine (Fo85) weathered microparticles under simulated current Martian surface conditions (pCO2 ∼ 7 mbar, UV (200–400 nm) flux ⁓ 2.3 W/m2). Our results demonstrate that chemical reactions under current Mars-like conditions facilitate hydration and transfer redox reactions of natural semiconducting minerals, driving the rapid formation of sulfates, iron oxides and amorphous silica within 72 h. These results highlight the role of natural semiconducting minerals in weathering processes under present-day Martian conditions. In addition, we performed geochemical simulations to evaluate the formation pathway of secondary minerals resulting from the weathering of pyrite-rich and pyrite-free basalt substrates during a transient warm episode on a generally cold and wet early Mars. Our models account for the contribution of oxidants to the Martian regolith via the spontaneous production of H2O2 in bulk water during the aqueous dissolution of pyrite microparticles. The models show differences in the types of secondary byproducts with sulfate and iron-oxide formation from pyrite weathering, especially during the cooling periods when gypsum formation increased significantly.